Diffusion Behaviors of Integrins in Single Cells Altered by Epithelial to Mesenchymal Transition (Small 5/2022). Issue 5 (3rd February 2022) - Yuan, Jing‐Wen; Zhang, Yu‐Ning; Liu, Yu‐Ru; Li, Wei; Dou, Shuo‐Xing; Wei, Yan; Wang, Peng‐Ye; Li, Hui
Abstract : Epithelial to Mesenchymal Transition The cover image shows that the malignant cells generated by the epithelial‐mesenchymal transition (EMT) are breaking away from the benign ones and spreading elsewhere. In article number 2106498, using single‐particle tracking of β1‐integrins labelled with fluorescent quantum dots, Yan Wei, Peng‐Ye Wang, Hui Li, and co‐workers discover a significantly enhanced diffusion of integrins on cell membranes after EMT, which may represent a new hallmark of EMT and offer a novel method for cancer diagnosis.